Single-cell analysis reveals transcriptomic features and therapeutic targets in primary pulmonary lymphoepithelioma-like carcinoma - Binghua Tan; Ke Xu; Yingcheng Lyu; Yicheng Liang; Ruihao Liang; Kai Lei; Jialu Liang; Jing Huang; Kefeng Wang; Duoguang Wu; Wenjian Wang; Xueting Hu; et al. (Communications Biology)
Abstract Primary pulmonary lymphoepithelioma-like carcinoma (PPLELC) is a rare subtype of non-small-cell lung cancer. Duo to the current lack of precise targeted therapies, there is an urgent need to identify novel therapeutic targets. In this study, we perform single-nucleus transcriptome analysis on PPLELC samples to reveal the molecular tumor heterogeneity and characterize the functional states of immune cells within the tumor microenvironment. We identify a critical malignant subpopulation of PPLELC characterized by elevated expression of AKT3 and FGFR2. Higher expression levels of AKT3 and FGFR2 are associated with poorer patient outcomes. Moreover, treatment with either an AKT3 inhibitor or an FGFR2 inhibitor significantly attenuates tumor progression in patient-derived xenograft models. Our findings highlight AKT3 and FGFR2 as potential therapeutic targets and prognostic biomarkers, providing valuable insights for the development of rational targeted therapies and immunotherapeutic strategies.